FINANCIAL STRESS AND ITS IMPACT ON RISKY CREDIT BEHAVIOUR: EVIDENCE FROM GENERATION Z PAYLATER USERS IN SUKABUMI - Selviana, Neng; Zulkarnain, Zulkarnain (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to examine the effect of financial stress on risky credit behaviour among Generation Z paylater users in Sukabumi City. A quantitative method was applied using a questionnaire distributed to 397 respondents. The data were analysed using multiple linear regression with SPSS 27. The results show that financial stress has a positive and significant effect on risky credit behaviour. This means that individuals experiencing higher financial stress tend to make impulsive financial decisions, such as borrowing excessively or delaying payments. The coefficient of determination (R²) value of 0.173 indicates that financial stress explains 17.3% of the variation in risky credit behaviour, while other factors explain the rest. This finding highlights the importance of managing financial pressure to prevent irresponsible credit usage among Generation Z in the digital era.